2019
DOI: 10.1016/s2214-109x(19)30279-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Chlamydia trachomatis in the Middle East and north Africa: a systematic review, meta-analysis, and meta-regression

Abstract: Background The epidemiology of Chlamydia trachomatis in the Middle East and north Africa is poorly understood. We aimed to provide a comprehensive epidemiological assessment of C trachomatis infection in the Middle East and north Africa. Methods We did a systematic review of C trachomatis infection as well as a meta-analysis and meta-regression of C trachomatis prevalence. We searched PubMed and Embase, as well as regional and national databases up to March 13, 2019, using broad search terms with no language o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 116 publications
2
44
3
Order By: Relevance
“…Notably, no small‐study effect, i.e. studies with smaller sample size yielding different antibody prevalence, was found. Similarly, the sampling method had no effect on observed antibody prevalence.…”
Section: Resultsmentioning
confidence: 83%
“…Notably, no small‐study effect, i.e. studies with smaller sample size yielding different antibody prevalence, was found. Similarly, the sampling method had no effect on observed antibody prevalence.…”
Section: Resultsmentioning
confidence: 83%
“…We showed CT infection was 5.0%. In Egypt, CT prevalence was 1.3%-52.0% among different categories of patients 37 . Our figure is parallel to El-Kettani et al 35 (3.8%) and Mosbah &Nabiel 38 (4.4%) figures', higher than El-Moselhy et al 27 (3.0%) and lower than Javanmard et al 39 (11.4%).…”
Section: Types Of Stismentioning
confidence: 95%
“…Univariable and multivariable random‐effects meta‐regressions were performed based on established methodology to assess predictors of HCV prevalence in populations with LRDs, trend in prevalence over time, and sources of between‐study heterogeneity. A priori relevant independent variables included type of population with LRDs, country, sample size (<100 or ≥10 to investigate a small‐study effect), year of data collection, and year of publication. The country variable included Egypt, Pakistan, and other MENA countries.…”
Section: Methodsmentioning
confidence: 99%